2021
DOI: 10.1002/cphc.202100202
|View full text |Cite
|
Sign up to set email alerts
|

Can Counter‐Intuitive Halogen Bonding Be Coulombic?

Abstract: We use the term “counter‐intuitive” to describe an intermolecular interaction in which the electrostatic potentials of the interacting regions of the ground‐state molecules have the same sign, both positive or both negative. In the present work, we consider counter‐intuitive halogen bonding with nitrogen bases, in which both the halogen σ‐hole and the nitrogen lone pair have negative potentials on their molecular surfaces. We show that these interactions can be treated as Coulombic despite the apparent repulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…Murray and Politzer [25] have recently reported a list of complexes that are formed between two neutral molecules, the acid of which contains a purportedly negative σhole. As evaluated on the 0.001 au isodensity surface, a V s,max as large as −10 kcal/mol was nonetheless able to engage in a stable complex, albeit only weakly so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murray and Politzer [25] have recently reported a list of complexes that are formed between two neutral molecules, the acid of which contains a purportedly negative σhole. As evaluated on the 0.001 au isodensity surface, a V s,max as large as −10 kcal/mol was nonetheless able to engage in a stable complex, albeit only weakly so.…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary to factor in charge transfer stabilization, and the ubiquitous attractive nature of dispersion forces. Some current literature bolsters these ideas with examples of stable halogen and chalcogen bonded complexes which were formed despite a negative σ-hole [23][24][25] in the Lewis acid molecule.…”
Section: Introductionmentioning
confidence: 98%
“…37 Furthermore, they have proposed that counterintuitive halogen bonding can be considered as coulombic where both polarization and the electrostatics play important roles. 38 A recent study of scaffold effects of different nitrogenbearing heterocycles on halogen bonding strength by Boeckler and co-workers used a local maximum of MESP on the molecular surface in close proximity to the s-hole, V Smax , as a descriptor for the magnitude of the s-hole. 39 Very recently Hoffmann et al reported a conceptual DFT study using electrophilicity indices to understand halogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…From a wider perspective, there is ample precedent for the idea that a σ‐hole is not a necessary condition for the formation of a stable noncovalent bond, and that a negative MEP in the binding region of a Lewis acid molecule can nonetheless engage in a stabilizing interaction with another molecule. Murray and Politzer [16] reported a list of complexes that are formed between two neutral molecules, the acid of which contains a negative σ‐hole. As a specific example, a series of calculations documented the ability of a molecule like H 2 T=Y, where T and Y respectively represent tetrel and chalcogen atoms, to engage in a chalcogen bond with a N‐base despite a σ‐hole of negative sign [17] …”
Section: Methodsmentioning
confidence: 99%